Site-Directed Mutagenesis of the Carotenoid Isomerase Gene BnaCRTISO Alters the Color of Petals and Leaves in Brassica napus L. - Li, Huailin; Yu, Kaidi; Amoo, Olalekan; Yu, Yalun; Guo, Mixia; Deng, Songyue; Li, Mengting; Hu, Limin; Wang, Jingzhen; Fan, Chuchuan; Zhou, Yongming (Frontiers in Plant Science, 2022)
The diversity of petal and leaf color can improve the ornamental value of rapeseed and promote the development of agriculture and tourism. The two copies of carotenoid isomerase gene (BnaCRTISO) in Brassica napus (BnaA09.CRTISO and BnaC08.CRTISO) was edited using the CRISPR/Cas9 system in the present study. The mutation phenotype of creamy white petals and yellowish leaves could be recovered only in targeted mutants of both BnaCRTISO functional copies, indicating that the redundant roles of BnaA09.CRTISO and BnaC08.CRTISO are vital for the regulation of petal and leaf color. The carotenoid content in the petals and leaves of the BnaCRTISO double mutant was significantly reduced. The chalcone content, a vital substance that makes up the yellow color, also decreased significantly in petals. Whereas, the contents of some carotenes (lycopene, α-carotene, γ-carotene) were increased significantly in petals. Further, transcriptome analysis showed that the targeted mutation of BnaCRTISO resulted in the significant down-regulation of important genes BnaPSY and BnaC4H in the carotenoid and flavonoid synthesis pathways, respectively; however, the expression of other genes related to carotenes and xanthophylls synthesis, such as BnaPDS3, BnaZEP, BnaBCH1 and BCH2, was up-regulated. This indicates that the molecular mechanism regulating petal color variation in B. napus is more complicated than those reported in Arabidopsis and other Brassica species. These results provide insight into the molecular mechanisms underlying flower color variation in rapeseed and provides valuable resources for rapeseed breeding.